2021
DOI: 10.1083/jcb.202006174
|View full text |Cite
|
Sign up to set email alerts
|

Reduced insulin/IGF1 signaling prevents immune aging via ZIP-10/bZIP–mediated feedforward loop

Abstract: A hallmark of aging is immunosenescence, a decline in immune functions, which appeared to be inevitable in living organisms, including Caenorhabditis elegans. Here, we show that genetic inhibition of the DAF-2/insulin/IGF-1 receptor drastically enhances immunocompetence in old age in C. elegans. We demonstrate that longevity-promoting DAF-16/FOXO and heat-shock transcription factor 1 (HSF-1) increase immunocompetence in old daf-2(−) animals. In contrast, p38 mitogen-activated protein kinase 1 (PMK-1), a key de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 66 publications
(108 reference statements)
3
22
0
Order By: Relevance
“…Dietary restriction appears to effectively regulate innate immunity and to extend lifespan, by its impact on the immunometabolic sensors, leading to gene reprogramming, as demonstrated in pre-clinical models [ 236 , 237 ]. In particular, caloric restriction increases sirtuin expression and modulates mTOR and other immunometabolic sensor pathways, thus reducing pro-inflammatory molecule levels [ 238 , 239 ].…”
Section: Research and Clinical Perspectivementioning
confidence: 99%
“…Dietary restriction appears to effectively regulate innate immunity and to extend lifespan, by its impact on the immunometabolic sensors, leading to gene reprogramming, as demonstrated in pre-clinical models [ 236 , 237 ]. In particular, caloric restriction increases sirtuin expression and modulates mTOR and other immunometabolic sensor pathways, thus reducing pro-inflammatory molecule levels [ 238 , 239 ].…”
Section: Research and Clinical Perspectivementioning
confidence: 99%
“…ins-6 promotes learning by stopping the expression of ins-7, an inhibitory factor (Chen et al 2013). As worms grow old, a feed-forward mechanism modulates the expression of ins-7, thereby regulating immune ageing and behaviour (Lee et al 2021b). Others, such as ins-11, are only expressed in adult worms following infection, either in the epidermis or the intestine, depending on the pathogen and its route of infection (Lee et al 2018).…”
Section: Feeling Sickmentioning
confidence: 99%
“…Our results suggest that the ISY-1/ mir-60 axis plays a gatekeeping role for ZIP-10 activation and phenoptosis, whereas the FLR-2/FSHR-1/GSA/KIN-2 axis is likely instructive by linking FTS stress to genes driving phenoptosis or promoting organismic sensitivity to lethal effects of FTS. FSHR-1 and ZIP-10 also mediate host cell responses to oxidative stress, various types of pathogens and immune aging (Kato et al, 2016; Lee et al, 2021; Miller et al, 2015; Powell et al, 2009). Indeed, we found that fshr-1 loss-of-function mutants, while being more FTS resistant than wild type, were less tolerant of cholesterol oxidative stress (Figure S4).…”
Section: Discussionmentioning
confidence: 99%